2009
DOI: 10.1007/s10817-009-9139-4
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Length Resolution Refutations of Difference Constraint Systems

Abstract: This paper is concerned with determining the optimal length resolution refutation (OLRR) of a system of difference constraints over an integral domain. The problem of finding short explanations for unsatisfiable difference constraint systems (DCS) finds applications in a number of design domains including program verification, proof theory, real-time scheduling and operations research. It is wellknown that resolution refutation is a sound and complete procedure to establish the unsatisfiability of boolean form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…We already know that if a DCS is unsatisfiable, then there must exist a simple negative cost cycle in the corresponding constraint network [Sub09]. The same applies for a WDCS.…”
Section: The Wolrr Problem (Add Rule)mentioning
confidence: 91%
See 4 more Smart Citations
“…We already know that if a DCS is unsatisfiable, then there must exist a simple negative cost cycle in the corresponding constraint network [Sub09]. The same applies for a WDCS.…”
Section: The Wolrr Problem (Add Rule)mentioning
confidence: 91%
“…A lot of the work in finding short refutations focuses on discrete domains. However, [Sub09] considers the problem of finding optimal length refutations for systems of difference constraints. In that paper it was shown that short refutations exist for difference constraints and also that the optimal length refutations for systems of difference constraints can be determined in polynomial time.…”
Section: Constraint Systemsmentioning
confidence: 99%
See 3 more Smart Citations